2012
DOI: 10.1186/1476-511x-11-62
|View full text |Cite
|
Sign up to set email alerts
|

Association of gender, ABCA1 gene polymorphisms and lipid profile in Greek young nurses

Abstract: ObjectiveOne of the important proteins involved in lipid metabolism is the ATP-binding cassette transporter A1 (ABCA1) encoding by ABCA1 gene. In this study we evaluated the single nucleotide polymorphisms (SNPs) of ABCA1 gene. We analyzed SNPs in chromosome 9 such as rs2230806 (R219K) in the position 107620867, rs2230808 (R1587K) in the position 106602625 and rs4149313 (I883M) in the position 106626574 according to gender and lipid profile of Greek nurses.MethodsThe study population consisted of 447 (87 men) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
2
14
0
1
Order By: Relevance
“…But no difference was observed in the level of TC. These results were similar to those of previous reports [17,18]. …”
Section: Discussionsupporting
confidence: 93%
“…But no difference was observed in the level of TC. These results were similar to those of previous reports [17,18]. …”
Section: Discussionsupporting
confidence: 93%
“…In analyses based on ethnicity, the association was still significant in Asians, but not in Caucasians. According to our previous [11] study from the young Greek women-nurses (living and working in the similar conditions) we did not find any association of R219K with demographic (smoking, waist circumference, BMI) or lipid parameters. Similarly in this study we have not observed any association of R219K gene polymorphism and demographic and lipid parameters.…”
Section: Discussionmentioning
confidence: 51%
“…In the present study, the mean HDL-C level was 1.6 mg/dL higher in KK genotype than in RR in men, and 1.0 mg/dL higher in KK than in RR in women. The mean difference between KK and RR genotypes varied from -0.4 to 19.0 mg/dL in Asian populations and from -15 to 3.1 mg/dL in Western populations [16,17]. In other representitive studies in Asians, the differences were 2.32 and 1.16 mg/dL in Li et al [18], 1.16 and 1.55 mg/dL in Li et al [19], and 4.65 and 1.55 mg/dL by Zhao and Xiao, respectively [20], while 0.77 and 0.39 mg/dL in Porchay-Balderelli et al in Caucasians [21].…”
Section: Discussionmentioning
confidence: 99%